2022
DOI: 10.1155/2022/6261528
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine‐N‐Oxide Alkaloids from Allium stipitatum and Their Synthetic Disulfide Analogs as Potential Drug Candidates against Mycobacterium tuberculosis: A Molecular Docking, QSBAR, and ADMET Prediction Approach

Abstract: In this study, we consider pyridine-N-oxide alkaloids from Allium stipitatum and their synthetic disulfide analogs (PDAs) as candidates for next-generational antimycobacterial agents, in light of growing resistance to existing conventional therapies. In silico studies involving molecular docking simulations of 12 PDAs were carried out against 7 Mycobacterium tuberculosis target proteins (MTs) to determine their theoretical binding affinities. Compounds A3, A6, and B9 demonstrated stronger binding affinities on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Furthermore, each of these drugs conforms to the Lipinski, Ghose, Verber, Egan and Muegge rules for orally active drugs and hence has the potential to be developed into oral medications. Apart from hepatotoxicity, druginduced cardiotoxicity is another often-reported adverse event that has resulted in drug withdrawal [41]; one source of drug-induced cardiotoxicity is inhibition of hERG (human ether-à-go-go-related gene) K + channels, which produces a type of fatal arrhythmia known as torsade de pointes or long QT syndrome [42]. Analysis of the optimal analogues suggested that they are neither cardiotoxic nor hepatotoxic (Table S4 and Table S5).…”
Section: Adme Prediction and Toxicitymentioning
confidence: 99%
“…Furthermore, each of these drugs conforms to the Lipinski, Ghose, Verber, Egan and Muegge rules for orally active drugs and hence has the potential to be developed into oral medications. Apart from hepatotoxicity, druginduced cardiotoxicity is another often-reported adverse event that has resulted in drug withdrawal [41]; one source of drug-induced cardiotoxicity is inhibition of hERG (human ether-à-go-go-related gene) K + channels, which produces a type of fatal arrhythmia known as torsade de pointes or long QT syndrome [42]. Analysis of the optimal analogues suggested that they are neither cardiotoxic nor hepatotoxic (Table S4 and Table S5).…”
Section: Adme Prediction and Toxicitymentioning
confidence: 99%
“…Alkaloids, present in most of the plants with activity against MTB, have a mechanism of action like isoniazid and pyrazinamide in MTB cell membrane, acting as efflux pump inhibitors, which hinders one of the main resistance mechanisms of MTB (AMENGOR et al, 2022). Some of these compounds have already gone to advanced stages of testing, such as thiliacorinin, nortiliacorinin and thiliacorin, which showed low MIC values such as 3.1 µg/mL, demonstrating that this class of compounds has great antimycobacterial potential (BOSE et al, 2021).…”
Section: Martins Et Al (2013) Carried Out Two Different Extractions O...mentioning
confidence: 99%
“…It is necessary to use multiple methods to explore dietary patterns and their associations with Mtb infection among close contacts in boarding colleges and universities to obtain a complete picture. The most common techniques used for dietary pattern extraction are a posteriori analyses, mainly principal component analysis (PCA), which takes observed correlations as the basis among dietary variables [4,10,13,14].…”
Section: Introductionmentioning
confidence: 99%